The dynamics of wage dispersion between firms: The role of firm entry and exit - Benedikt Schröpf (Friedrich-Alexander-Universität Erlangen-Nürnberg, Lehrstuhl für Arbeitsmarkt- und Regionalpolitik, 2021)
Although wage inequality is a prominent and widely studied issue, the literature is vastly silent on the relationship between firm entry and exit and the wage dispersion between firms. Using a 50% random administrative sample of West German establishments over the period 1976-2017, I study wage dispersion dynamics between and within the groups of entering, exiting and incumbent establishments by examining the distribution of average wages across establishments. The results show that entering establishments became increasingly unequal over time, thereby contributing to the rise in the wage dispersion between establishments. However, stronger exit dynamism of young and low-wage establishments has dampened this effect. These findings suggest taking the consequences for wage inequality into consideration when designing and assessing policy instruments for firm entry and exit. – – Obwohl Lohnungleichheit ein bedeutendes und umfassend untersuchtes Thema ist, bleibt der Zusammenhang zwischen Firmengründungen und-schließungen und der Lohnstreuung zwischen Firmen in der Literatur weitgehend unerwähnt. Anhand einer 50%igen administrativen Zufallsstichprobe westdeutscher Betriebe im Zeitraum 1976-2017 studiere ich die Dynamik der Lohnstreuung zwischen und innerhalb neu gegründeter, schließender und etablierter Betriebe, indem ich dieVerteilung der betrieblichen Durchschnittslöhne untersuche. Die Ergebnisse zeigen,dass die Ungleichheit zwischen den neu gegründeten Betrieben im Laufe der Zeit zugenommen hat, was zum Anstieg der Lohnstreuung zwischen den Betrieben beigetragen hat. Eine stärkere Schließungsdynamik bei jungen Niedriglohnbetrieben hat diesen Effekt jedoch gedämpft. Diese Ergebnisse legen nahe, die Folgen für dieLohnungleichheit bei der Gestaltung und Bewertung von politischen Maßnahmen zu Firmengründungen und -schließungen zu berücksichtigen.
Keywords: L26; M13; J31; 330; Firm entry; Firm exit; Wage dispersion; Firm Dynamics; Germany